Sosialisasi Pemanfaatan Smart Digital Untuk Peningkatan Penjualan UMKM Dengan Menggunakan Aplikasi Gofood Di Desa Japanan Kecamatan Kemlagi Kabupaten Mojokerto - Anna Kridaningsih; Ghozali Ghozali; Elok Cahyaning Pratiwi (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
MSMEs are currently required to be able to improve their business by using technological developments, so the aim of this service is to provide socialization on the use of smart digital to increase MSME sales by using the GoFood application in Japanan Village, Kemlagi District, Mojokerto Regency. The method used in this community service consists of three stages, namely, the initial stage, the implementation stage and the final stage. The result of this community service is that socialization has been carried out by delivering material about the importance of smart digital to increase sales, and about the use of the GoFood application to support sales. The hope of this activity is that it can be implemented so that an increase in sales of Japanese village MSMEs can be achieved.